Anti-osteoporotic treatments in the era of non-alcoholic fatty liver disease: friend or foe - Chondrogianni, Maria Eleni; Kyrou, Ioannis; Androutsakos, Theodoros; Flessa, Christina-Maria; Menenakos, Evangelos; Chatha, Kamaljit Kaur; Aranan, Yekaterina; Papavassiliou, Athanasios G.; Kassi, Eva; Randeva, Harpal S. (Frontiers in Endocrinology, 2024)
Over the last years non-alcoholic fatty liver disease (NAFLD) has grown into the most common chronic liver disease globally, affecting 17-38% of the general population and 50-75% of patients with obesity and/or type 2 diabetes mellitus (T2DM). NAFLD encompasses a spectrum of chronic liver diseases, ranging from simple steatosis (non-alcoholic fatty liver, NAFL) and non-alcoholic steatohepatitis (NASH; or metabolic dysfunction-associated steatohepatitis, MASH) to fibrosis and cirrhosis with liver failure or/and hepatocellular carcinoma. Due to its increasing prevalence and associated morbidity and mortality, the disease-related and broader socioeconomic burden of NAFLD is substantial. Of note, currently there is no globally approved pharmacotherapy for NAFLD. Similar to NAFLD, osteoporosis constitutes also a silent disease, until an osteoporotic fracture occurs, which poses a markedly significant disease and socioeconomic burden. Increasing emerging data have recently highlighted links between NAFLD and osteoporosis, linking the pathogenesis of NAFLD with the process of bone remodeling. However, clinical studies are still limited demonstrating this associative relationship, while more evidence is needed towards discovering potential causative links. Since these two chronic diseases frequently co-exist, there are data suggesting that anti-osteoporosis treatments may affect NAFLD progression by impacting on its pathogenetic mechanisms. In the present review, we present on overview of the current understanding of the liver-bone cross talk and summarize the experimental and clinical evidence correlating NAFLD and osteoporosis, focusing on the possible effects of anti-osteoporotic drugs on NAFLD.